2012
DOI: 10.1891/1933-3196.6.4.174
|View full text |Cite
|
Sign up to set email alerts
|

Stop the Use of Eye Movements in Resource Development and Installation, Until Their Additional Value Has Been Proven: A Rejoinder to

Abstract: This brief article responds to Leeds and Korn's (2012) commentary on our article in which we found that eye movements (EMs) during recall of positive and resourceful autobiographic memories (such as those used in resource development and installation [RDI]) led to decreases of (a) vividness, (b) pleasantness, and (c) experienced strength of the intended quality or resource. Hence, we found an opposite effect than what was intended and critically discussed this in our article. In their comments, Leeds and Korn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Hornsveld et al reported that BLS decreases vividness, pleasantness, and experiences of strength of the intended quality or resource [ 13 14 ]. They suggested not using BLS in RDI because BLS may disturb RDI [ 15 ]. However, Leeds and Korn advocated the use of BLS as an important element in the standard RDI protocol [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hornsveld et al reported that BLS decreases vividness, pleasantness, and experiences of strength of the intended quality or resource [ 13 14 ]. They suggested not using BLS in RDI because BLS may disturb RDI [ 15 ]. However, Leeds and Korn advocated the use of BLS as an important element in the standard RDI protocol [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some modifications have been made to the original EMDR protocol to take into account recent literature, e.g. no eye movements in the safe place protocol [ 43 ]. In addition, a restriction has been placed on types of unblocking strategies particularly those using imagery during the interweave to prevent contamination of the treatment condition.…”
Section: Methodsmentioning
confidence: 99%
“…Within the AIP framework, time spent deliberately installing positive resources is thought to make these ideas more 'available' to adaptive processing within EMDR. Despite some controversy regarding mechanisms [59][60][61], resource development techniques have been widely accepted amongst clinicians (e.g. Steinert [62]), and RDI is described in the third edition of the EMDR key text [54].…”
Section: Resource Development and Installation And Other Techniques F...mentioning
confidence: 99%